Corporate Entrepreneurship and Organizational Performance - Abdulrahaman, Salmanulfarisi; Garba, Abubakar S. (NIU Journal of Humanities, 2020)
The aim of this study is to investigate the effect of corporate entrepreneurship on organizational performance in Dangote group. Descriptive survey research design was used while a sample size of two hundred and thirty eight (238) respondents using Sloveneâ€™s formula were selected out of 592 management staff of Dangote group using  stratified-proportionate sampling.  A Closed-ended questionnaire using 4 Likertâ€™s rating scale was distributed, the instrument was tested using face validity, and to check the internal consistence, test and retest method was employed.  Pearson Linear Correlation and Multiple Regression analysis was use to analyze the data using Statistical Package for Social Science (SPSS) version 21.  The overall results of the study revealed that innovativeness and risk taking have no positive relationship with organizational performance, while pro-activeness has positive and significant effect on organizational performance in Dangote Group Nigeria. The study recommends that the management should pay attention to proacativeness when increasing organizational performance in Dangote Group. Keywords: Corporate Entrepreneurship, Organizational Performance, Innovativeness, Risk Taking, customer care and Interpersonal Relation